Environmental Leadership, Green Innovation Practices, Environmental Knowledge Learning, and Firm Performance. (May 2020) - Su, Xiaofeng; Xu, Anxin; Lin, Wenhe; Chen, Youcheng; Liu, Songtao; Xu, Wenxing
Environmental leadership has received continuous attention from the business sector in recent years, yet few studies have examined the internal mechanisms and contingent conditions that link environmental leadership to firm performance. The aim of this article is to advance research by investigating the relationship between environmental leadership and firm performance by considering the mediating role of green innovation practices and the moderating role of environmental knowledge learning. A questionnaire survey is used to collect data from 353 agricultural products corporations in China. Empirical results show that environmental leadership has a positive relationship with the two dimensions of firm performance, namely, environmental performance and financial performance. Results also indicate that green innovation practices (including green innovation strategy and actions) play a mediating role between environmental leadership and firm performance. Meanwhile, it is also found that environmental knowledge learning positively moderates the effect of environmental leadership on green innovation practices. This study adds value to the environmental management literature by introducing leadership style as an antecedent variable to examine the impact of environmental leadership on firm performance in China. And the study also highlights the important moderating effect of environmental knowledge learning on the relationship between environmental leadership and green innovation practices. The findings of this article could be important in terms of both management and policy implications.